Detection of tubercle bacilli in Ziehl-Neelsen stained tissue slide images using Hu’s moment invariants and artificial neural network - Mohammad Khusairi, Osman; Mohd Yusoff, Mashor, Prof. Dr.; Hasnan, Jaafar (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Perlis, Malaysia.